Reply to “Correspondence: Androgen receptor mRNA in glioblastoma: a reliable marker of tumor burden or a statistical artefact?” - Larysa Liubych; Lorenz Hahn; Raja Hollnagel; Maria Karolin Streubel; Deepak Ailani; Jan Leppert; Harald Krenzlin; Jakob Matschke; Celina Soltwedel; Nicole Borgardt; Susanne Behling; Oksana Zemskova; et al. (Molecular Biology Reports, 2026)

Androgen receptor expression in glioblastoma: molecular profiling and association with tumor burden - Larysa Liubych; Lorenz Hahn; Raja Hollnagel; Maria Karolin Streubel; Deepak Ailani; Jan Leppert; Harald Krenzlin; Jakob Matschke; Celina Soltwedel; Nicole Borgardt; Susanne Behling; Oksana Zemskova; et al. (Molecular Biology Reports, 2026)

Assessing plant belowground decomposability: comparing experimental and observational approaches - Szilvia Márta Neumann; Eva Janíková; Marie Konečná; Tereza Švancárová; Markéta Applová; Petr Blažek; Aleš Lisner; Amira Fatime Vörös; Johannes H. C. Cornelissen; Lars Götzenberger; Jan Lepš; Jules Segrestin (Plant and Soil, 2026)

Signal and feature reconstruction in structural health monitoring under varying environmental conditions - Lizzie Neumann; Philipp Wittenberg; Alexander Mendler; Jan Gertheiss (Engineering Structures, 2026)

Impact of root observation windows on plant performance, root development, and rhizosphere-microbial communities during late vegetative growth of field-grown winter wheat - Loreen Sommermann; Jan Helge Behr; Narges Moradtalab; Saskia Windisch; Soumitra Paul Chowdhury; Michael Rothballer; Ingo Schellenberg; Doreen Babin; Kornelia Smalla; Lorrie Maccario; SØren J. SØrensen; Uwe Ludewig; et al. (Plant and Soil, 2026)
Background and Aims Root observation windows (RW) installed in the field provide a tool for non-destructive monitoring of root development and rhizosphere processes. However, the highly invasive installation process, which requires cutting soil profiles, may affect plant development and, ultimately, the outcome of the experiments. This study systematically compares plant development with and without the installation of RW. Methods Using the location of a long-term field experiment, the responses of winter wheat to different intensities of tillage, N-fertilization, and use of fungicides were compared for plants grown along root windows and in undisturbed control plots. Sampling was performed during late vegetative growth, six weeks after RW installation, with comparisons of shoot and root biomass, root length, mineral nutritional status, stress-related gene expression, stress metabolites, and the composition of microbial communities reflecting rhizosphere (RH) conditions. Results The presence of RW did not significantly affect most of the parameters analyzed. As an exception, RW plants showed increased foliar concentrations of several nutrients (K, Mg, Ca, Cu, Mn), potentially attributable to reduced inter-plant competition because RW were installed along border rows of the experimental plots. By contrast, N-fertilization intensity and fungicide use affected plant biomass, root growth, and fungal communities. Tillage intensity primarily affected fine-root production, the composition of RH-microbial communities, and physiological stress indicators in leaf tissue. Conclusion The results suggest only a limited influence on performance of winter wheat six weeks after RW installation under the selected experimental conditions, with plant responses and experimental results comparable to undisturbed controls.

On indirect negative inotropic effects of muscarine in the isolated human atrium - Joachim Neumann; Britt Hofmann; Katarina Hadova; Jan Klimas; Ulrich Gergs (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)
Acetylcholine, the physiological agonist at all muscarinic receptors, alone (“direct effect”) or after pre-stimulation with isoprenaline (“indirect effect”), is known to reduce the force of contraction (FOC) in human atrial preparations (HAP). We hypothesized that muscarine might act similar to acetylcholine. During open heart surgery for severe coronary heart disease, HAP were obtained. Using digital polymerase chain reaction, we noted that the messenger ribonucleic acid (mRNA) of the M 1 -, M 2 -, and M 3 -muscarinic receptors in HAP contributed to 0.09%, 96.34%, and 3.57%, respectively, of the total mRNA expression of the combined mRNA expression of the sum of the M 1 -, M 2 -, and M 3 -muscarinic receptors. The HAP were mounted in organ baths, electrically stimulated (1 Hz) and FOC was measured under isometric conditions. When given alone, muscarine transiently reduced FOC. After application of 1 µM isoprenaline (to stimulate β-adrenoceptors) or 1 µM serotonin (to stimulate 5-HT 4 -serotonin receptors) or 1 µM histamine (to stimulate H 2 -histamine receptors) or 10 µM fenoldopam (to stimulate D 1 -dopamine receptors) or 100 nM semaglutide (to stimulate glucagon-like-peptide-1 receptors) or 100 nM gastric inhibitory peptide (to stimulate the gastric inhibitory peptide receptors) additionally applied 1 µM muscarine reduced FOC. Interestingly, after 1 µM forskolin (to stimulate adenylyl cyclase independent of receptor involvement), 1 µM cilostamide (to inhibit cAMP degradation) or 100 µM dibutyryl-cAMP (to directly stimulate the cAMP-dependent protein kinase), additionally applied 1 µM muscarine also reduced FOC. We conclude that muscarine in the presence of several cAMP-increasing agents or a cAMP-dependent protein kinase activating agent exerts negative inotropic effects in HAP. These contractile responses might underlie negative inotropic effects in muscarine intoxications in the clinic.

Mechanisms of systolic heart failure in PP2CxPP5 double transgenic mice - Rebecca Schwarz; Katarina Hadova; Jan Klimas; Igor Buchwalow; Joachim Neumann; Ulrich Gergs (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)
The function importance of serine threonine phosphatases (PP) in the heart is still subject of investigations. For instance, PP5 and PP2C occur in the human heart. It is unclear how they interact in the human heart. In order to obtain a model system, we have crossbred mice with heart-specific overexpression of PP2C or PP5 to obtain wild-type mice (WT), PP2C transgenic mice (PP2C-TG), PP5 transgenic mice (PP5-TG), and PP2CxPP5 double transgenic mice (DT). Moreover, while PP2C-TG and PP5-TG did not show any increase in relative heart weight, it was increased in DT. In histology, DT showed cardiac fibrosis based on Masson/Goldner staining compared to WT. Basal ejection fraction was reduced in PP5-TG by 25%, by 29% in PP2C-TG, and by 38% of WT values in DT. This went hand in hand with a diminished phosphorylation of phospholamban at serine-16, the phosphorylation site for the cAMP-dependent protein kinase (PKA), after perfusion of isolated hearts with isoprenaline. DT and PP2C-TG sustained ischemia and reperfusion of isolated hearts worse than WT or PP5-TG. Expression of atrial natriuretic factor (ANF, marker of hypertrophy), of collagen 1a (fibrosis marker) and nuclear factor kappa B (marker of inflammation) in DT were augmented versus WT (ANF: 5.14 ± 0.75 vs. 1.00 ± 0.33; Col1a1: 1.82 ± 0.09 vs. 1.00 ± 0.10; Nfkb1: 1.33 ± 0.03 vs 1.00 ± 0.04; n = 6–10; p < 0.05). In summary, cardiac co-overexpression of two PPs, namely, PP2C and PP5, was detrimental to cardiac function. The underlying (patho)mechanism for this may involve dephosphorylation of Ca 2+ regulatory proteins but also accompanying fibrosis and inflammation.

Corrigendum to “Quality-assurance of heat-flow data: the new structure and evaluation scheme of the IHFC Global Heat Flow Database” [Tectonophysics 863 (2023) / 229976] - Sven Fuchs; Ben Norden; Florian Neumann; Norbert Kaul; Akiko Tanaka; Ilmo T. Kukkonen; Christophe Pascal; Rodolfo Christiansen; Gianluca Gola; Jan Šafanda; Orlando Miguel Espinoza-Ojeda; Ignacio Marzan; et al. (Tectonophysics, 2026)

Protein phosphatase 2A impairs cardiac uptake of glucose in the mammalian heart - Katarina Hadova; Daniel Gündel; Torsten Knieß; Peter Brust; Jan Klimas; Joachim Neumann; Ulrich Gergs (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)
Protein phosphatase 2A (PP2A) accounts for approximately half of all serine/threonine phosphatase activity in the mammalian heart. We hypothesised that PP2A, through dephosphorylation of key regulatory enzymes, modulates cardiac glucose uptake and metabolism in vivo. Using positron emission tomography (PET), we studied the uptake of 2-[ 18 F]fluoro-2-deoxy-D-glucose ([ 18 F]FDG) in living mice with cardiac-specific overexpression of the catalytic subunit of PP2A (PP2A-TG) as well as in littermate controls (wild-type, WT). Additionally, we analysed the expression of enzymes and transcription factors involved in cardiac glucose metabolism. Cardiac glucose consumption was reduced by 41% ( P < 0.05) in PP2A-TG mice relative to WT. Real-time quantitative polymerase chain reaction analysis revealed decreased gene expression of glycogen synthase 1 (− 26%, P < 0.05), glycogen phosphorylase (− 17%, P < 0.05), Mtor (-22%, P < 0.05), peroxisome proliferator-activated receptor gamma (Pparg), and its coactivator PGC-1α (-41% and − 28% respectively; both P < 0.05) in PP2A-TG hearts. Western blotting demonstrated increased protein expression of phosphoinositide 3-kinase (PI3K, 26%, P < 0.05), reduced expression of glycogen synthase (-34%, P < 0.05) and glycogen phosphorylase (-18%, P < 0.05), and enhanced phosphorylation of AKT (95%, P < 0.05) and glycogen synthase kinase-3β (GSK3β, 22%, P < 0.05) in PP2A-TG hearts. These findings indicate that PP2A impairs cardiac glucose metabolism in vivo through modulation of multiple components of glucose handling, including the PI3K/AKT signalling axis, glycogen metabolism, and PPARγ-dependent transcriptional regulation. The effects of PP2A appear to be predominantly indirect. Elevated PP2A expression may therefore be detrimental in heart failure by compromising myocardial energy production.

Initial characterization of M2-muscarinic receptor overexpressing mouse heart - Ulrich Gergs; Igor B. Buchwalow; Britt Hofmann; Jaromir Myslivecek; Katerina Janisova; Katarina Hadova; Franziska Schettler; Max Keller; Jan Klimas; Joachim Neumann (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)
There are five muscarinic receptor subtypes expressed in the human heart. The main subtype is the M 2 -muscarinic receptor. We hypothesized that overexpression of the M 2 -muscarinic receptor should augment any contractile effects that are M 2 -muscarinic receptor–mediated. Therefore, we generated a transgenic mouse with overexpression of the human M 2 -muscarinic receptor under the control of the heart-specific α-myosin heavy chain promoter (M 2 -TG). We performed contraction experiments with electrically stimulated (1 Hz) left atrial preparations (LA) and spontaneously beating right atrial preparations (RA) from adult M 2 -TG or from adult wild-type littermate mice (WT). We confirmed the expression of the human M 2 -muscarinic receptor in the mouse heart by reverse transcription polymerase chain reaction (RT-PCR) and radioligand binding experiments at cardiac membranes and tissue sections. We did not detect differences in hematoxylin/eosin staining or Masson/Goldner staining between M 2 -TG and WT. We noticed that carbachol (10 nM–10 µM cumulatively applied) alone or in the presence of 1 µM isoprenaline reduced the force of contraction (FOC) to a similar extent in LA from M 2 -TG and WT. The beating rate in RA was similarly decreased by carbachol alone or by carbachol in the presence of 1 µM isoprenaline in M 2 -TG and WT. Overall, the number of RA that displayed absolute arrhythmias was higher in atria from M 2 -TG compared to atria from WT. No arrhythmias were noted in LA from M 2 -TG or WT. Stimulation of human M 2 -muscarinic receptors induced absolute atrial arrhythmias more often in RA from M 2 -TG than in RA from WT. Overexpressed M 2 -muscarinic receptors were silent to the force and beating rate.

Intraspecific differences in leaf decomposition and associated traits in closely related Carex species: a microcosm experiment - Szilvia Márta Neumann; Jules Segrestin; Marie Konečná; Aleš Lisner; Markéta Applová; Petr Blažek; Anna E-Vojtkó; Eva Janíková; Lars Götzenberger; Jan Lepš (Oecologia, 2025)
Litter decomposition is a fundamental process in carbon and nutrient cycling in terrestrial ecosystems. In a microcosm experiment we investigated the determinants of leaf decomposition with consideration of the 'afterlife’ effect hypothesis, which suggests a connection between green leaf traits and the decomposability of leaf material. We collected senesced litter and living leaves of individuals of four Carex species widely distributed in the Czech Republic. We aimed to determine the extent of intra- and interspecific variability in decomposition rates ( k values), whether species ranking was consistent along environmental gradients and whether intraspecific trait variability affected litter decomposability, as we would expect from the 'afterlife’ effect hypothesis. While litter quality and decomposition rates significantly differed between fresh leaves and litter, species identity explained a prominent amount of variability in both. The effect of populations was around a tenth of species identity’s, nonetheless still significant. Environmental variables and leaf traits generally showed rather weak or non-significant correlations with decomposition rates, which suggests that within closely related species ecological preferences might not be correlated with leaf decomposability, nor the conditions of individual localities are modifying tissue quality in a way to affect decomposability. While the correlation between fresh leaf and litter decomposition rates was not very strong (r = 0.51), fresh leaves provided a fair prediction of litter decomposition. However, considering the pattern of intra- and interspecific differences in decomposition rates, and the quality of fresh leaves and litter, using litter to determine leaf decomposability might give more realistic results.

Semi-variograms provide superior spatial and temporal insights into artificial rainfall compared to Christiansen uniformity - Jan-František Kubát; Martin Neumann; Petr Kavka (Journal of Hydrology, 2025)

Stimulation of histamine H1-receptors produces a positive inotropic effect in the human atrium - Thanh Hoai Pham; Lina Maria Rayo Abella; Katarina Hadova; Jan Klimas; Stefan Dhein; Steffen Pockes; Jonas Manfred Albert Schlicht; Britt Hofmann; Uwe Kirchhefer; Joachim Neumann; Ulrich Gergs (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)
There is a controversy whether histamine H 1 -receptor activation raises or lowers or does not affect contractility in the human heart. Therefore, we studied stimulation of H 1 -receptors in isolated electrically stimulated (one beat per second) human atrial preparations (HAP). For comparison, we measured force of contraction in left atrial preparations (LA) from mice with overexpression of the histamine H 1 -receptor in the heart (H 1 -TG). We detected the messenger ribonucleic acid (mRNA) expression of human histamine H 1 -receptors in HAP. In LA from H 1 -TG, each cumulatively applied concentration of histamine and a dual H 1 /H 2 -agonist called 2-(2-thiazolyl)-ethylamine (ThEA) caused a time-dependent initial negative inotropic effect followed over time by a lasting positive inotropic effect. Both effects were concentration-dependent in LA from H 1 -TG. After 100 µM cimetidine, 10 µM histamine exercised a positive inotropic effect in HAP that was diminished by 10 µM mepyramine, an H 1 -receptor antagonist. The concentrations of mepyramine and cimetidine used here are based on the work of others and our own work (e.g., Guo et al. J Cardiovasc Pharmacol. 6:1210-5 1984, Rayo Abella et al. J Pharmacol Exp Ther. 389:174-185 2024). Similarly, we observed that ThEA (10 µM, 30 µM, 100 µM cumulatively applied) induced a concentration- and time-dependent positive inotropic effect in HAP. In HAP, we detected never negative inotropic effects to either histamine or ThEA. The positive inotropic effects to ThEA in HAP were reduced by mepyramine. The positive inotropic effects of ThEA in LA from H 1 -TG and in HAP were not accompanied by reductions in the time of tension relaxation. We conclude that stimulation of histamine H 1 -receptors only increases and does not decrease force of contraction in the HAP in our patients.

Initial characterization of a transgenic mouse with overexpression of the human D1-dopamine receptor in the heart - Lina Maria Rayo Abella; Hannes Jacob; Christin Hesse; Britt Hofmann; Sarah Schneider; Lisa Schindler; Max Keller; Igor B. Buchwalow; CongYu Jin; Pertti Panula; Stefan Dhein; Jan Klimas; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)
Dopamine can exert effects in the mammalian heart via five different dopamine receptors. There is controversy whether dopamine receptors increase contractility in the human heart. Therefore, we have generated mice that overexpress the human D 1 -dopamine receptor in the heart (D 1 -TG) and hypothesized that dopamine increases force of contraction and beating rate compared to wild-type mice (WT). In D 1 -TG hearts, we ascertained the presence of D 1 -dopamine receptors by autoradiography using [ 3 H]SKF 38393. The mRNA for human D 1 -dopamine receptors was present in D 1 -TG hearts and absent in WT. We detected by in-situ-hybridization mRNA for D 1 -dopamine receptors in atrial and ventricular D 1 -TG cardiomyocytes compared to WT but also in human atrial preparations. We noted that in the presence of 10 µM propranolol (to antagonize β-adrenoceptors), dopamine alone and the D 1 - and D 5 -dopamine receptor agonist SKF 38393 (0.1–10 µM cumulatively applied) exerted concentration- and time-dependent positive inotropic effects and positive chronotropic effects in left or right atrial preparations from D 1 -TG. The positive inotropic effects of SKF 38393 in left atrial preparations from D 1 -TG led to an increased rate of relaxation and accompanied by and probably caused by an augmented phosphorylation state of the inhibitory subunit of troponin. In the presence of 0.4 µM propranolol, 1 µM dopamine could increase left ventricular force of contraction in isolated perfused hearts from D 1 -TG. In this model, we have demonstrated a positive inotropic and chronotropic effect of dopamine. Thus, in principle, the human D 1 -dopamine receptor can couple to contractility in the mammalian heart.

Quality-assurance of heat-flow data: The new structure and evaluation scheme of the IHFC Global Heat Flow Database - Sven Fuchs; Ben Norden; Florian Neumann; Norbert Kaul; Akiko Tanaka; Ilmo T. Kukkonen; Christophe Pascal; Rodolfo Christiansen; Gianluca Gola; Jan Šafanda; Orlando Miguel Espinoza-Ojeda; Ignacio Marzan; et al. (Tectonophysics, 2023)

The interplay of temperature and algal enrichment intensifies bioturbation of the intertidal amphipod Corophium volutator - Eilish M. Farrell; Jan Beermann; Andreas Neumann; Alexa Wrede (Journal of Experimental Marine Biology and Ecology, 2023)

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Anaerobic treatment of residuals from tanks transporting food and fodder - Van Than Nguyen; Erik Beyer; Jan Neumann; Dirk Awe; Wolfgang Pfeiffer; Jens Tränckner (Environmental Science and Pollution Research, 2019)

Quantification of PpIX-fluorescence of cerebral metastases: a pilot study - Johannes Knipps; Igor Fischer; Lisa M. Neumann; Marion Rapp; Maxine Dibué-Adjei; Christiane Freiin von Saß; Jan-Malte Placke; Hendrik-Jan Mijderwijk; Hans-Jakob Steiger; Michael Sabel; Jan-Frederick Cornelius; Marcel A. Kamp (Clinical & Experimental Metastasis, 2019)

Darbepoetin inhibits proliferation of hepatic cancer cells in the presence of TGF-β - Sabrina Ehnert; Thomas Freude; Carmen Eicher; Britta Burkhardt; Juan J. Martínez Sánchez; Jan Neumann; Ruben Mühl-Benninghaus; Steven Dooley; Stefan Pscherer; Andreas K. Nussler (Archives of Toxicology, 2014)

Information content of female copulation calls in wild long-tailed macaques (Macaca fascicularis) - Antje Engelhardt; Julia Fischer; Christof Neumann; Jan-Boje Pfeifer; Michael Heistermann (Behavioral Ecology and Sociobiology, 2012)

Comparative analysis of phase I and II enzyme activities in 5 hepatic cell lines identifies Huh-7 and HCC-T cells with the highest potential to study drug metabolism - Jie Lin; Lilianna Schyschka; Ruben Mühl-Benninghaus; Jan Neumann; Liping Hao; Natascha Nussler; Steven Dooley; Liegang Liu; Ulrich Stöckle; Andreas K. Nussler; Sabrina Ehnert (Archives of Toxicology, 2012)

Toxicity of octameric elemental sulphur in aquatic sediments - Mathias Ricking; Helga Neumann-Hensel; Jan Schwarzbauer; Anders Svenson (Environmental Chemistry Letters, 2004)

Chromosome Sorting and PCR-Based Physical Mapping in Pea (Pisum Sativum L.) - Pavel Neumann; Dana Pozárková; Jan Vrána; Jaroslav Doležel; Jiří Macas (Chromosome Research, 2002)